Sins of Omission: Are junior doctors failing to report clinical incidents, and if so, how can we better support them to do so?. Issue 5 (September 2021) - Bertram, Ian; Cantelo, Jack; Hutton, William; Kirkham, Henry; Scallan, Nicholas
Objectives: University Hospitals Birmingham's (UHB) Foundation Doctors should log clinical incidents via the Trust's incident reporting system. Anecdotal reports suggest under-reporting is commonplace. It is therefore important to identify the proportion of Foundation Year 1 (FY1s) who witnessed but did not report incidents and identify and weigh perceived barriers to reporting. We can then suggest strategies to address these barriers and repeat our data collection. Methodology: We performed an analysis of anonymised data from the Trust's Datix Incident Reporting system alongside an anonymised survey to determine the proportion of FY1s witnessing reportable clinical incidents, and the proportion successfully reporting an incident in the 2017/18 academic year. The survey also gathered data on FY1 perceptions of barriers to reporting. We went on to discuss our results with UHB management and suggested several strategies to improve reporting, prior to repeating data collection for the 2019–20 academic year. Results: 36.4% FY1 doctors surveyed in 2017–18 reported witnessing at least one clinical incident that they did not report. 37.0% FY1 doctors surveyed in 2019–20 reported the same. Respondents felt time taken to complete forms and system complexity were the key barriers to reporting. Conclusion: Results show that over a third of FY1s at UHB had witnessed but not reported at least one clinical incident each year. The evidence-based strategies suggested to the trust in 2018 and 2020 included FY1 education on incident reporting, early senior clinician involvement in the reporting pathway, and a streamlined reporting system integrated with existing infrastructure. These have not been implemented.